In memory of Viktor Danylovych Omelchenko (May 14, 1944—August 29, 2022) - Verpahovska, O.O.; Starostenko, V.I.; Legostaeva, O.V.; Chulkow, S.S. (Geofizicheskiy Zhurnal, 2022)
In memory of Viktor Danylovych Omelchenko (May 14, 1944—August 29, 2022)